Chiral phononic crystal-inspired railway track for low-frequency vibration suppression - Qu, Shuai (2024)
Chiral phononic crystals (CPCs) offer an advanced approach to vibration isolation by exploiting inertial amplification, establishing broad band gaps at low frequencies and outperforming conventional phononic designs. This study pioneers a CPC-inspired railway track that significantly enhances low-frequency vibration isolation through an orthogonal polarization coupling mechanism of the chiral subunit cell. Mechanical modeling and simulations have validated the causes of the enhanced performance and the tunability of crucial physical parameters across characteristic dimensions. Incorporating this structure within a coupled vehicle-floating slab track (FST)-tunnel system facilitates a comparative analysis against conventional steel spring FSTs. The CPC-inspired track system demonstrates enhanced isolation, significantly reducing vibrations within the 200 Hz range for both slab and tunnel structures, achieving a maximum insertion loss of 7.19 dB for the slab and 5.69 dB for the tunnel. Further evaluation of rail and slab displacements, alongside the wheel load reduction rate, underscores the operational safety of trains with the CPC-inspired system implemented. This pioneering exploration of CPC-inspired structures showcases the potential to significantly advance vibration control in urban rail infrastructure, providing a foundational reference for future research.